Charged premium for the extension of coverage period from 5th March, 2020 to 31st December, 2022 - Bangladesh General Insurance Company Ltd. (BGIC) (Brac University, 2023)
This record consists of general correspondence regarding Contractor's All Risk (CAR) insurance policy between Brac University and BUCG for BRACU new campus project.